IOT based Drowsiness Detection System for Road Safety - M. , Nithya; T. , Narmadha; R. , Hariharan (International Journal of Psychosocial Rehabilitation, 2020)
In the current situation, the vehicle utilization rate is expanding. Thus, the quantity of mishaps is additionally expanding. As per the look into it, most of the mishaps are because of the driver’s recklessness. Every year, among them all, the number of deaths is 1.24 million because of vehicle mishaps. In India, the underlying drivers of these mishaps are the inebriated driver, drowsiness, and severely structured speed breakers. There is no viable system to forestall these main drivers. Our proposed framework gives a proficient, practical, and constant answer for forestalling vehicle mishaps. In this paper, we proposed a framework that is completely non-meddlesome and constant. Our proposed framework utilized the eye conclusion proportion as an information parameter to recognize the drowsiness of the driver. On the off chance that the eye conclusion proportion breaks down from the standard proportion, the driver is alerted with the assistance of a ringer. For our framework, a Pi camera is utilized to catch the pictures of the driver’s eye, and the whole framework is consolidated utilizing Raspberry Pi. At long last SMS alert was sent to the proprietor’s mobile.